IMF Committee on Balance of Payments Statistics : Annual Report 2003. (Balance of Payments Statistics; Balance of Payments Statistics ;, 2004)
The IMF Committee on Balance of Payments Statistics was established in1992 for the following purposes: to oversee the implementation of the recommendations contained in the reports of two IMF working parties that investigated the principal sources of discrepancy in global balance of payments statistics published by the IMF;t o advise the IMF on methodological and compilation issues in the context of balance of payments and international investment position statistics; and to foster greater coordination of data collection among countries. This slim volume is the official report of the Committee's sixteenth meeting in December 2003 in Washington, D.C.